2012
DOI: 10.1002/iroh.201111510
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of water temperature and nutrients concentration on periphyton respiration – implications of global change

Abstract: With the increase in global mean surface temperature predicted for the near future, stream water temperature will also increase. Simultaneously, water quality is likely to decrease (e.g., due to increases in nutrient and pollutant concentrations). The objective of this study was to evaluate the individual and combined effects of increases in water temperature and nutrients concentration on periphyton respiration, as a surrogate for stream metabolism. Stones naturally colonized with periphyton in an unpolluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Temperature is a key factor in the development of algal biomass because it regulates cellular metabolism, tending to optimize growth rates (Bowes et al, 2007). Normally, nitrogen and phosphorus act as limiting nutrients for algae and periphyton growth in stream ecosystems (Murdock et al, 2011;Rosa et al, 2013). In streams located near agricultural areas, the periphyton production can be increased by input of fertilizers leached from surrounding areas (Conley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature is a key factor in the development of algal biomass because it regulates cellular metabolism, tending to optimize growth rates (Bowes et al, 2007). Normally, nitrogen and phosphorus act as limiting nutrients for algae and periphyton growth in stream ecosystems (Murdock et al, 2011;Rosa et al, 2013). In streams located near agricultural areas, the periphyton production can be increased by input of fertilizers leached from surrounding areas (Conley et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The extract retained in the trays was stored in covered centrifuge tubes (50 ml) under refrigeration and taken to the laboratory. After the periphyton was removed, the active surface area of each cobble, i.e., the area excluding the lower surface, was determined following Rosa et al (2013) Sample processing. The chlorophyll-a content was used as an indicator of the growth of periphytic algae on each incubated cobble.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was found that increasing overlying water velocity promoted establishment of a more physiologically active consortium of bacterial denitrifiers in periphyton (Arnon et al, 2007). Stimulation of periphyton respiration was observed by increased temperature and nutrient concentrations (Rosa et al, 2013).…”
Section: Introductionmentioning
confidence: 95%